Review of Berliner & Biddle "The Manufactured Crisis" - Stedman, Lawrence C. (Education Policy Analysis Archives, 1996)
In a provocative new book, The Manufactured Crisis, David Berliner and Bruce Biddle make four sweeping claims about U.S. achievement: there never was a test score decline, today's students are "out-achieving their parents substantially" (p. 33), U.S. students "stack up very well" in international assessments (p. 63), and the general education crisis is a right-wing fabrication. As a progressive, I'm sympathetic to their concerns, but as a scholar who specializes in this material, I find their analysis deeply flawed and misleading. They mischaracterize the test score decline data, mishandle the international findings, and fail to acknowledge students' continuing low levels of academic achievement.